Interoperability of CABRI Services and Biochemical Pathways Databases. Issue 2 (2004) - Romano, Paolo; Aresu, Ottavia; Assunta Manniello, Maria; Parodi, Barbara
Abstract : Common Access to Biological Resources and Information (CABRI) service is a 'one-stop-shop' for materials that are collected by a number of European culture collections that engage themselves in a quality service for the scientific community by adhering to Quality Guidelines for the management of resources and related information. It includes collections' catalogues that can be searched in an SRS implementation. A simple search facility, including a synonym search and a shopping cart, is also available. Within the European Biological Resource Centres Network (EBRCN) project, an extension and improvement of the catalogues' information is under way. This includes adding links to bibliographic databanks and sequence databases. Revision of 'in-house' controlled vocabularies used by data annotators is under way, in order to improve the setting up of external links, and new links to biochemical pathways databases are being set up for some of the catalogues.